Prevention and treatment of HIV infection in neonates: evidence base for existing WHO dosing recommendations and implementation considerations - Diana F. Clarke (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Introduction: Antiretroviral drugs are used in neonates for prevention and treatment of HIV infection. Use of antiretrovirals to prevent perinatal HIV transmission is well established. Early identification of neonates infected with HIV and rapid initiation of combination antiretroviral treatment during the neonatal period is now recommended by WHO and DHHS. However, few antiretrovirals are available in formulations suitable for neonates and there are limited safety and pharmacokinetic data for most antiretrovirals in neonates. Areas covered: We summarize existing neonatal antiretroviral safety and pharmacokinetic information and discuss implementation considerations for programs providing antiretrovirals to neonates and young infants. Expert commentary: Antiretrovirals currently recommended by WHO for use in neonates are zidovudine, lamivudine, lopinavir/ritonavir, nevirapine, and raltegravir. Significant implementation challenges exist to the widespread use of these antiretrovirals in neonates. Optimal, feasible treatment of HIV-exposed and HIV-infected newborns will require development of practical neonatal dosage forms and their study in neonates for a wide range of antiretrovirals.